"The grass is greener on the other side": The relationship between the Brexit referendum results and spatial inequalities at the local level. Issue 6 (5th October 2021) - Gutiérrez‐Posada, Diana; Plotnikova, María; Rubiera‐Morollón, Fernando
Abstract: Despite seven decades of development of the European Union project, on 23 June 2016, the United Kingdom, Europe and the rest of the world were surprised when the Leave campaign won the Brexit referendum, offering an extraordinary case study for researchers. We spatially disaggregate the vote share data, which allows us to explore where anti‐European sentiment took root in the UK and why. In this paper, a spatial dependence model is applied to clarify and quantify the relevance of the different dimensions—demographic, cultural/educational and economic—that play a role in explaining the rise of support for the Leave campaign. The analysis is conducted at the local level, using local authorities (LAs) as the spatial unit of analysis due to the combination of official datasets with newly generated data in the context of an EU H2020 project. A new indicator capturing the affluence of each local area relative to its close neighbours is proposed and included in the model. In general, we observe that most of the main conclusions obtained by large regions or at the national level also hold at the local scale. However, it is particularly interesting that inequalities by LAs are clearly significant, indicating a marked influence on voters' decisions that have thus far been unaccounted for. This result provides further support for the existence of, to use Andrés Rodriguez‐Pose's terminology, an even more intense "revenge of the places that do not matter" at the local scale. Resumen: A pesar de siete décadas de desarrollo del proyecto de la Unión Europea, el 23 de junio de 2016, el Reino Unido, Europa y el resto del mundo se vieron sorprendidos cuando la campaña Leave ganó el referéndum de Brexit, lo que ofreció un estudio de caso extraordinario para la investigación. En este artículo se desagregaron espacialmente los datos de distribución del voto, lo que permitió examinar en dónde arraigó el sentimiento antieuropeo en el Reino Unido y por qué. Se aplicó un modelo de dependencia espacial para aclarar y cuantificar la relevancia de las diferentes dimensiones (demográfica, cultural/educativa y económica) que intervienen en la explicación del aumento del apoyo a la campaña Leave . El análisis se realizó a nivel local, utilizando las autoridades locales (AL) como unidad espacial de análisis debido a la combinación de conjuntos de datos oficiales con datos recién generados en el contexto de un proyecto Horizonte 2020 de la UE. Se propone un nuevo indicador que capta la prosperidad de cada área local en relación con sus vecinas cercanas, que se incluyó en el modelo. En general, se observó que la mayoría de las conclusiones principales obtenidas por las grandes regiones o a nivel nacional aplican también a escala local. Sin embargo, es especialmente interesante que las desigualdades a nivel de AL son claramente significativas, lo que indica una marcada influencia en las decisiones de los votantes que hasta ahora no se han tenido en cuenta. Este resultado proporciona apoyo adicional a la existencia de, según la terminología de Andrés Rodríguez‐Pose, una "venganza de los sitios que no importan" aún más intensa a escala local. 抄録: 欧州連合(EU)のプロジェクトが70年にわたって進展してきたにもかかわらず、2016年6月23日に英国のEU離脱の是非を問う国民投票では離脱運動が勝利したが、英国をはじめ、欧州、その他の国々はその結果に驚き、研究者らに特別なケーススタディを提供することとなった。我々は、得票率のデータを空間的に分析することにより、英国のどの地域に反EU感情が根付いたのか、またその理由を探索する。本稿では、空間依存モデルを用いて、離脱運動の支持率上昇の原因となる様々な側面(人口統計学的、文化的/教育的および経済的)の重要性を明らかにし、定量化する。地方当局(local authority:LA)を、EUのホライズン2020プロジェクトのなかで新たに生成されたデータと公式データセットの組み合わせによる分析の空間単位として用いて、地域レベルでの分析を実施する。隣接する地域と比較した各地域の豊かさを測る新しい指標を提案し、分析モデルに含めた。概して、大規模な地域や国レベルで得られた主な結論のほとんどは、地域規模にも当てはまると考えられる。しかし、LA間での不平等は明らかに重大であり、これまで明らかにされなかった有権者の意思決定に大きな影響を与えていることを示しており、非常に興味深い。この結果は、Andrés Rodriguez‐Poseの言葉を借りれば、地域規模ではさらに激しい「revenge of the places that do not matter(重要ではない場所の復讐)」が存在することをより強く裏付けるものである。